2011
DOI: 10.1111/j.1471-0528.2011.03170.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vault drainage on postoperative morbidity after vaginal hysterectomy for benign gynaecological disease: a randomised controlled trial

Abstract: Please cite this paper as: Dua A, Galimberti A, Subramaniam M, Popli G, Radley S. The effects of vault drainage on postoperative morbidity after vaginal hysterectomy for benign gynaecological disease: a randomised controlled trial. BJOG 2011; DOI: 10.1111/j.1471‐0528.2011.03170.x. Objective  To evaluate the efficacy of vault drainage in reducing the immediate postoperative morbidity associated with vaginal hysterectomy carried out for benign gynaecological conditions. Design  Randomised controlled trial. Setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Recently, studies have shown that use of a bipolar vessel sealing system is associated with a lower risk of vault haematoma . However, no proven benefit was identified for routine vault drainage …”
Section: Vaginal Vault Complicationsmentioning
confidence: 99%
“…Recently, studies have shown that use of a bipolar vessel sealing system is associated with a lower risk of vault haematoma . However, no proven benefit was identified for routine vault drainage …”
Section: Vaginal Vault Complicationsmentioning
confidence: 99%
“…Generally, a pelvic drain is placed to reduce postoperative morbidity by facilitating the removal of gas and pelvic fluid collection, to assess fluid characteristics, to check for any unsuspected hemorrhages in the surgical field, and to promote tissue apposition and wound healing without the need for further invasive procedures. A randomized study by Dua et al 12 suggested that the routine use of vault drainage during vaginal hysterectomy did not influence febrile morbidity, but there were no adverse outcomes noted with the use of the drain. The volume of fluid that may be drained even after extensive pelvic dissection using laparoscopy is unpredictable, and the decision to use postoperative drainage was based on the surgeon’s experience and the patient’s clinical condition.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative febrile morbidity was defined as a body temperature ≥ 37.5° C, a definition that has been used previously in a number of studies assessing postoperative infectious morbidity. 11 12 Temperature was measured every 4 hours in the postoperative ward, excluding the 1 st day after surgery. If a body temperature ≥ 37.5° C was noted on any postoperative day, we confirmed febrile status by checking the temperature hourly two times and appropriately controlling the fever.…”
Section: Methodsmentioning
confidence: 99%
“…At present, there is paucity of data regarding the preferred cuff closure technique for vaginal hysterectomy. A trial assessing routine use of a vault drain during vaginal hysterectomy for benign disorders did not show any significant effect on postoperative morbidity [12]. Another study evaluated closure of the peritoneum and vaginal epithelium aiming to obliterate the space above the vaginal cuff and thereby reduce the incidence of vaginal vaults hematomas.…”
Section: Commentmentioning
confidence: 99%